Collaborative tasks for online language teaching - González‐Lloret, Marta (Foreign language annals, 2020)
Online language teaching has become a reality for many foreign language programs that have been forced to teach remotely. When developing an online language teaching curriculum (beyond a simple emergency teaching patch), it is important to uphold the same rigor and base our curriculum in methodological and pedagogic choices based on second language acquisition and educational research, and keep in mind that interaction is critical to developing second language skills. This article advocates that, through collaborative technology‐mediated tasks, we can promote productive language output (spoken and written) and the type of interaction that facilitates language learning and motivates students to continue improving their language skills. The Challenge Meaningful learner interaction is critical to developing second language skills. However, this can be challenging in a digital environment. What are some tasks that facilitate interaction and build learner community when teaching and learning online?